Rheumatiod Factor isotype in Rheumatiod Arthritis patients . - Abbas, Nahida R.; Mousawy, Khalidh M.; Khafaji, Jassim T. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Rheumatiod factor in patients with Rheumatoid arthritis (RA) could be of IgM, IgG, or IgG isotypes. Aim: To study the occurance of each or all these isotypes in RA patients . Methods: Enzyme linked Immune Sorbent Assay (ELISA) & Latex agglutination test were used to asses RF in 74 patients with RA. Results: Using ELISA, 58 (78.4%) patients had positive RF (IgM 48.6%, IgG in 47.3% & IgA in 54.1% ), while only 43 (58.1) patients were positive by AG . Conclusion All RF isotypes should be assessed in patients with RA.